Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Erratum to ‘Gestational inhalation of nanoparticles alters placental glucose transporter expression and increases glucose flux in rats’ [Toxicol. Appl. Pharmacol. 515 (2026) 117996] - Talia N. Seymore; Sara Hoffmann; Pedro Louro; Carol Gardner; Michael J. Goedken; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Gestational exposure to micro and nanoplastics differentially impacts cardiac development and function in male and female rats throughout the lifespan - Chelsea M. Cary; Samantha Adams; Gina M. Moreno; Talia N. Seymore; Marianne Polunas; Michael J. Goedken; Xiang Wang; Edward J. Yurkow; Phoebe A. Stapleton (Toxicology and Applied Pharmacology, 2025)

Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Identification of micro- and nanoplastic particles in postnatal sprague-dawley rat offspring after maternal inhalation exposure throughout gestation - Gina M. Moreno; Tanisha Brunson-Malone; Samantha Adams; Calla Nguyen; Talia N. Seymore; Chelsea M. Cary; Marianne Polunas; Michael J. Goedken; Phoebe A. Stapleton (Science of The Total Environment, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Assessment of the Applicability of Capsid-Integrity Assays for Detecting Infectious Norovirus Inactivated by Heat or UV Irradiation - David I. Walker; Lisa J. Cross; Tina A. Stapleton; Connaire L. Jenkins; David N. Lees; James A. Lowther (Food and Environmental Virology, 2019)

Use of F-Specific RNA Bacteriophage to Estimate Infectious Norovirus Levels in Oysters - J. A. Lowther; L. Cross; T. Stapleton; N. E. Gustar; D. I. Walker; M. Sills; S. Treagus; V. Pollington; D. N. Lees (Food and Environmental Virology, 2019)

Creative Solution for Implementation of Experiential, Competency-Based Palliative Care Training for Internal Medicine Residents - Douglas D. Ross; Deborah W. Shpritz; Susan D. Wolfsthal; Ann B. Zimrin; Timothy J. Keay; Hong-Bin Fang; Carl A. Schuetz; Laura M. Stapleton; David E. Weissman (Journal of Cancer Education, 2011)

Effects of temperature variation on suicide in five U.S. counties, 1991–2001 - P. G. Dixon; A. N. McDonald; K. N. Scheitlin; J. E. Stapleton; J. S. Allen; W. M. Carter; M. R. Holley; D. D. Inman; J. B. Roberts (International Journal of Biometeorology, 2007)

Irradiance-induced changes in the photobiology of Halophila johnsonii - J. I. Kunzelman; M. J. Durako; W. J. Kenworthy; A. Stapleton; J. L. C. Wright (Marine Biology, 2005)

The fate of 15 N added to high Arctic tundra to mimic increased inputs of atmospheric nitrogen released from a melting snowpack - A. M. Tye; S. D. Young; N. M. J. Crout; H. M. West; L. M. Stapleton; P. R. Poulton; J. Laybourn‐Parry (Global Change Biology, 2005)
Increases in the long‐range aerial transport of reactive N species from low to high latitudes will lead to increased accumulation in the Arctic snowpack, followed by release during the early summer thaw. We followed the release of simulated snowpack N, and its subsequent fate over three growing seasons, on two contrasting high Arctic tundra types on Spitsbergen (79°N). Applications of 15 N (99 atom%) at 0.1 and 0.5 g N m −2 were made immediately after snowmelt in 2001 as either Na 15 NO 3 or 15 NH 4 Cl. These applications are approximately 1 × and 5 × the yearly atmospheric deposition rates. The vegetation at the principal experimental site was dominated by bryophytes and Salix polaris while at the second site, vegetation included bryophytes, graminoids and lichens. Audits of the applied 15 N were undertaken, over two or three growing seasons, by determining the amounts of labeled N in the soil (0–3 and 3–10 cm), soil microbial biomass and different vegetation fractions. Initial partitioning of the 15 N at the first sampling time showed that ∼60% of the applied 15 N was recovered in soil, litter and plants, regardless of N form or application rate, indicating that rapid immobilization into organic forms had occurred at both sites. Substantial incorporation of the 15 N was found in the microbial biomass in the humus layer and in the bryophyte and lichen fractions. After initial partitioning there appeared to be little change in the total 15 N recovered over the following two or three seasons in each of the sampled fractions, indicating highly conservative N retention. The most obvious transfer of 15 N, following assimilation, was from the microbial biomass into stable forms of humus, with an apparent half‐life of just over 1 year. At the principal site the microbial biomass and vascular plants were found to immobilize the greatest proportion of 15 N compared with their total N concentration. In the more diverse tundra of the second site, lichen species and graminoids competed effectively for 15 NH 4 ‐N and 15 NO 3 ‐N, respectively. Results suggest that Arctic tundra habitats have a considerable capacity to immobilize additional inorganic N released from the snow pack. However, with 40% of the applied 15 N apparently lost there is potential for N enrichment in the surrounding fjordal systems during the spring thaw.

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Nicotine availability from Eclipse tobacco-heating cigarette - J. A. Stapleton; Michael A. H. Russell; Gay Sutherland; Colin Feyerabend (Psychopharmacology, 1998)

Improvement of soil solarization with volatile compounds generated from organic Amendments - A. Gamliel; J. J. Stapleton (Phytoparasitica, 1997)